Improving the packaging material availability for internal testing - A case study at Tetra Pak - Karlsson,Madeleine; Jönsson,Jennie (2023)
Title: Improving the packaging material availability for internal testing - A case study at Tetra Pak Keywords: Supply chain management, process mapping, procurement, visibility, order handling, supply chain information systems. Background: For any business, optimizing the supply chain is beneficial and can be a crucial competitive advantage. Additionally, the significance of optimization is even greater for the elements that are most essential for one's business offering and value creation. An essential element in the business offering at Tetra Pak is the internal testing required to develop and deliver high quality processing and packaging solutions. It has been identified that there are improvement areas in this process. A deeper understanding of the current process is desired, to evaluate and improve the process. Purpose: The purpose of this thesis is to improve the coordination of packaging material for internal testing at Tetra Pak. Research questions: To improve the current setup and coordination of packaging material for internal testing, the following research questions have been answered: • How does the current process of coordinating packaging material for internal testing look like? • How can the efficiency of the coordination of packaging material for internal testing be increased? • How can the performance of the coordination of packaging material for internal testing be measured? Method: This study is based on a single case study where the coordination of packaging material for internal testing is the unit of analysis. The project has a predominant focus on a deductive approach since existing theory has been reviewed to investigate the phenomenon. Qualitative and quantitative data is collected to then be structured and analyzed through performing a Makigami analysis. Conclusion: The Makigami analysis has visualized the process including responsible functions, where they are operating in the process, and respective functions needs. The entire process is complex with many exceptional cases and where the outcome varies depending on the situation. Commonly, there are shortcomings in collaboration, a lack of training materials throughout the process and a lack of understanding between the functions involved and their individual work process.
Keywords: Supply chain management; process mapping; procurement; visibility; order handling; supply chain information systems.